Kajian Pendekatan Simultan Tingkat Kesehatan Bank Konvensional dengan CAMELS dan RGEC - Yusnita Octafilia; Evelyn Wiyaja (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to analyze conventional health bank level by using CAMELS and RGEC methods. This is descriptive research of quantitative approach with conventional banks as samples as fifty banks from 2012 to 2017. The results of this study shows that ratios of CAMELS method are in from 1 to 3 composite level mostly where CAR, NIM, BOPO are in very good condition and ROA, NPM, LDR, ROE are in quite good condition. Then, in RGEC method, conventional health bank level has value from 1 to 5 composite level commonly where CAR, NIM, BOPO are in very adequate condition and NPL, IRR tend to show quite adequate condition while GCG tends to show unadequate condition. Finally, conventional helth bank level by using CAMELS and RGEC methods are in composite level between 1-3 mostly. It means that conventional health bank level of Indonesia in very good or very adequate and quite good or quite adequate condition. Keywords : Banking Health Level, Conventional, CAMELS, RGEC